Komunikasi Kepemimpinan dalam Perubahan Organisasi Pemerintah - Yudie Aprianto; Wahyudi Kumorotomo; Rajiyem Rajiyem (Universitas Gadjah Mada, 2023)
An organization experiences changes on a constant basis. The institution is driven to adapt and survive in this competitive environment by both internal and external stimuli. To manage organisational change, leaders play a crucial role. However, more research is still needed in the field of how leaders react and communicate in the context of organizational change, particularly in the public institution. In explaining leadership communication in organizational change, existing studies frequently use widely accepted views such as leadership styles that frequently contradict one another. Therefore, this research aims to investigate how leadership communication is carried out in the context of organizational change. How a public organization prepares for and integrates into a new government organization is investigated using qualitative and interpretive methods with a case study method. The role of leadership communication in managing organizational change was examined from a sensemaking point of view. In order to gain a complete picture of leadership communication, 17 participants were interviewed at different organizational levels. By demonstrating how leaders navigate an organization's managerial change discourse by integrating their bracketed information from various relevant sources, choosing information, and reconstructing information through communication, this article makes a valuable contribution to the literature on leadership communication.